2003
DOI: 10.1002/pros.10238
|View full text |Cite
|
Sign up to set email alerts
|

Expression and function of pro‐inflammatory interleukin IL‐17 and IL‐17 receptor in normal, benign hyperplastic, and malignant prostate

Abstract: Activated BPH-T-cells abundantly express IL-17. The increase of IL-17 in BPH-tissues goes hand in hand with elevated levels of IL-15, a pro-inflammatory cytokine with T-cell growth factor properties. A clinical relevance of increased IL-17 expression under pathological conditions is suggested by the demonstration of significant upregulation of IL-6 and IL-8 production of prostatic SC by IL-17.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
159
0
6

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 219 publications
(170 citation statements)
references
References 43 publications
5
159
0
6
Order By: Relevance
“…They showed that activated T cells in BPH tissue and in prostate cancer express high levels of IL17 (REF. 85). Further work to more fully elucidate the phenotypic and biological properties of all T-cell subsets in the prostate is required before we can understand the significance of acquired cellmediated immunity in prostate carcinogenesis.…”
Section: Immunobiology Of Prostate Inflammationmentioning
confidence: 99%
“…They showed that activated T cells in BPH tissue and in prostate cancer express high levels of IL17 (REF. 85). Further work to more fully elucidate the phenotypic and biological properties of all T-cell subsets in the prostate is required before we can understand the significance of acquired cellmediated immunity in prostate carcinogenesis.…”
Section: Immunobiology Of Prostate Inflammationmentioning
confidence: 99%
“…haematopoietic tumours in immunocompetent mice) [112,113] of tumours in experimental animals. Although the role of IL-17 in tumour biology is unclear and evidence remains conflicting, IL-17 can be detected in some (such as ovarian, skin and prostatic cancers) [114][115][116] but not all (e.g. acute myeloid leukaemia) [117] human tumours and one emerging theme is that, when present, it promotes angiogenesis [111,114], for example through the up-regulation of angiogenic factors such as CXCL1, CXCL5, CXCL6 and CXCL8 [118], thereby facilitating tumour growth and invasion.…”
Section: Systemic Lupus Erythematosis (Sle) and Other Conditionsmentioning
confidence: 99%
“…Indeed, as testosterone lymphocytes progressively accumulate, IL4 and IL13 expression increases, suggesting a shift toward a Th0/Th2 immune response (Steiner et al 2003a). There is also evidence that a loss of tolerance to self-antigens, associated with expansion of Th17 cells and IL17 overexpression, is crucial in BPH development (Steiner et al 2003b). This is also supported by the observation that IL8 and IL6, key executors of stromal growth in BPH, are produced by prostatic stromal cells in response to IL17 (Penna et al 2009), thus linking a self-perpetuating autoimmune response to altered tissue remodeling and hyperplastic growth (Ropiquet et al 1999).…”
Section: Introductionmentioning
confidence: 99%